Does licensing promote innovation?. Issue 2 (17th February 2020) - Colombo, Stefano
ABSTRACT: We analyse the impact of licensing on the equilibrium amount of cost-reducing innovation under several licensing mechanisms in the case of a duopoly model with heterogeneous firms. Under a wide class of licensing mechanisms, we find that as product substitutability increases, the possibility of higher innovation under licensing compared to no licensing decreases. Therefore, firms' heterogeneity is crucial to assess whether licensing incentivizes or not R&D cost-reducing investments.